Routledge handbook of sexuality, health and rights - Aggleton, Peter; Parker, Richard Guy (Routledge, 2010)
This handbook surveys the state of the discipline, including examination and discussion of emerging, controversial and cutting edge areas. It is an essential reference for all academics and researchers in the fields of sexuality studies, sexual health and human rights, as well as very useful reading for more advanced students.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; droits; outils; ouvrages de références; périodes historiques; santé; santé reproductive; sexualité; thématiques